Circadian Variations in Natural Coagulation Inhibitors Protein C, Protein S and Antithrombin in Healthy Men: A Possible Association with Interleukin-6 - Ündar, Levent; Ertugğrul, Cemal; Altunbas, Hasan; Akça, Serdar (Thrombosis and Haemostasis, 1999)
Recent observations describe an increase in platelet aggregability and a decrease in fibrinolytic activity in the early morning hours. To determine whether anticoagulant proteins also show such a circadian variation we measured protein C (PC), protein S (PS), antithrombin (AT) and heparin cofactor-II (HC-II) levels on venous plasma samples taken from 10 healthy men at three-hour intervals throughout a 24-hour period. To investigate the possible temporal mapping of circadian periodicity, we also measured plasma levels of beta-thromboglobulin (β-TG) as an indicator of platelet activation, and interleukin-6 (IL-6) as one of the possible regulatory factors that drive this rhythm.Blood samples were drawn at 6 a.m., 9 a.m., noon, 3 p.m., 6 p.m., 9 p.m. and midnight. PC, IL-6 and β-TG were measured by ELISA, PS and AT by latex immune assay and HC-II by chromogenic substrate method. A significant circadian variation was found in PC, PS, AT, β-TG and IL-6, but not in HC-II levels. PC, PS, IL-6 and β-TG were at their peaks at 6 a.m., and nadirs at a time from noon to midnight. AT peak was at 6 p.m. and nadir at noon. The regression of PS on IL-6 was significant. Although the fluctuations of PS and AT were within the normal ranges during the day, some PC levels of two subjects were below the lower normal limit (0.70).These data indicate that PC, PS, and AT show a marked circadian periodicity as the other components of the blood coagulation and fibrinolytic system do. The similar trends in plasma concentrations of PC, PS, β-TG and IL-6 may be coincidental, but could reflect a common regulatory mechanism or an effect on each other. The clinical implications of these physiological changes in coagulation inhibitors and the role of IL-6 in the anticoagulant response deserve further studies.